Samoa : 2021 Article IV Consultation-Press Release and Staff Report. (IMF Staff Country Reports; Country Report ;, 2021)
Samoa has shown resilience to past economic shocks, underpinned by the authorities' strong commitment to support the economy and financial assistance provided by the international community. Samoa was among the first countries in the world to secure its border to protect its citizens from COVID-19. The authorities' quick response to the measles outbreak and the global pandemic has identified the policy priorities well. The international community also responded swiftly, including the IMF disbursement under the Rapid Credit Facility (RCF) in April 2020 which helped unlock record budget support grants by the Asian Development Bank (ADB) and the World Bank (WB). The authorities strengthened the health care system and provided support to the private sector, with assistance targeted to vulnerable businesses and households to safeguard livelihoods.